Stratigraphic evolution and characteristics of lobes : a high-resolution study of Fan 3, Tanqua Karoo, South Africa - Neethling, J. M. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Earth Sciences))--University of Stellenbosch, 2009.